Dietary Inflammatory Index and its Association with the Risk of Cardiovascular Diseases, Metabolic Syndrome, and Mortality: A Systematic Review and Meta-Analysis - Namazi, Nazli; Larijani, Bagher; Azadbakht, Leila (Hormone and Metabolic Research, 2018)
Findings from previous studies on the association between the Dietary Inflammatory Index (DII) and the risk of chronic diseases and mortality have been inconsistent. We aimed to summarize studies on the association of the DII and the risk for cardiovascular disease (CVD), metabolic syndrome (MetS), and mortality in a systematic review and meta-analysis. We performed a systematic search in PubMed/Medline, Web of Knowledge, and Scopus databases for relevant studies written in English and published until 31 December 2017. Studies that reported the relative risk (RR), odd ratio (OR) or hazard ratio (HR) for the most pro-inflammatory versus the most anti-inflammatory diets were included. Finally, 17 studies [CVD (n=6), MetS (n=5), mortality (n=6)] were included for systematic review and meta-analysis. Findings indicated a trend toward a positive relationship between the DII and the risk for CVD (pooled RR: 1.35; 95% CI: 1.13, 1.60; I2: 28.6%, p=0.21), all-cause mortality (pooled HR: 1.21; 95% CI: 1.09, 1.35; I2: 72.6%, p=0.003), CVD mortality (pooled HR: 1.30, 95% CI: 1.07, 1.57; I2: 74.0%, p=0.009) and cancer mortality (pooled HR: 1.28; 95% CI: 1.07, 1.53; I2: 62.5%, p=0.03). However, no significant association was found between the DII and the risk for MetS (pooled RR: 1.01; 95% CI: 0.82, 1.24; I2: 32.6%, p=0.20). Although in the current meta-analysis the most pro-inflammatory diet versus the most anti-inflammatory diet was not associated with the risk of MetS, we observed a substantial association between the DII and the risk for CVD and all types of mortality. However, further cohort studies in different populations are needed to clarify this association.
Keywords: inflammation; cardiovascular disease; metabolic syndrome; death